2020
DOI: 10.1002/adfm.202009217
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Energy Storage Enabled Magnetically Actuated, Octopus‐Inspired Smart Adhesive

Abstract: Octopus suckers offer remarkable adhesion performance against nonporous surfaces and have inspired extensive research to develop artificial adhesives. However, most of existing octopus‐inspired adhesives are either passive without an actuation strategy or active but not energy efficient. Here, a novel design of a magnetically actuated, energy‐efficient smart adhesive with rapidly tunable, great switchable, and highly reversible adhesion strength inspired by the elastic energy storage mechanism in octopus sucke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 65 publications
0
71
0
Order By: Relevance
“…Subsequent work found that the reversible adhesion can be realized by imitating ratchet-like attachment mechanism of climbing plants. [18] Recently, smart adhesives inspired by natural animals have been developed, such as the magnetically actuated elastic energy storage adhesives inspired by octopus suckers, [19] the gecko inspired wedged surface utilized for dry adhesion, [20] tree frog inspired hierarchical structure, and insect inspired fibrillar pads for enhanced wet adhesion [21,22] and mussel inspired tissue adhesive hydrogel for sensors. [23] Despite extensive studies on artificial adhesives, they often need to introduce nondegradable cross-linking agent along with complex and time-consuming manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work found that the reversible adhesion can be realized by imitating ratchet-like attachment mechanism of climbing plants. [18] Recently, smart adhesives inspired by natural animals have been developed, such as the magnetically actuated elastic energy storage adhesives inspired by octopus suckers, [19] the gecko inspired wedged surface utilized for dry adhesion, [20] tree frog inspired hierarchical structure, and insect inspired fibrillar pads for enhanced wet adhesion [21,22] and mussel inspired tissue adhesive hydrogel for sensors. [23] Despite extensive studies on artificial adhesives, they often need to introduce nondegradable cross-linking agent along with complex and time-consuming manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] In this process, the device is transferred by adjusting the interface strength. [ 42,43 ] To increase the transfer printing yield rate, different materials and structures have been used, such as stamps with reversible boundary tips, [ 44 ] temperature‐response microstructures, [ 45 ] magnetically actuated microstructures [ 46 ] gecko feet‐like microstructures, [ 47 ] and stamps made of water response hydrogels. [ 48 ] For a better contact mode, Corbett et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dexterous cephalopods with soft arms and distributed suction cups provide bionic solutions since they can adsorb and release wet and dry objects in different sizes and shapes with ease [1][2][3][4]. In recent years, many researchers have been devoted to designing and fabricating novel bio-inspired suction cups [5][6][7][8][9][10][11][12][13][14][15][16]. Nguyen et al [5] fabricated an adhesive pad covered by a distributed passive suction cups array, which showed a three-times higher suction force than the theoretical limit, available for both dry and wet surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To grasp objects of irregular shapes and in confined environments, Mazzolai et al [9] designed and fabricated a soft arm mimicking octopuses' tentacles, which consists of an elastic arm made by polydimethylsiloxane and a pneumatically actuated suction cup array. Besides the conventional passive and fluid actuated suction cups, some researchers attempted to employ new actuation mechanisms [11,[15][16][17]. Lee et al [11] fabricated micro suction cups, of which the inner chamber is covered by temperature-sensitive hydrogel, Polymers 2021, 13, 3481 2 of 12 changing the chamber volume under different temperatures and reversely switching the adhesive force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation